当前位置:网站首页>Infix expression to suffix expression

Infix expression to suffix expression

2020-11-08 18:11:43 Shura God Tang San

(1) First determine the expression expression A The order of operations , Then add brackets :((1 + (( 2 + 3)* 4 )) – 5 )

(2) Start with the innermost bracket , The conversion method to suffix expression is :( Ignore brackets ) The number is in front , The sign is after .

1)( 2 + 3) => 23+

2) (( 2 + 3)* 4 ) => 23+4*

3) (1 + (( 2 + 3)* 4 ))=> 123+4*+ [ In order of operation , From left to right ]

4)((1 + (( 2 + 3)* 4 )) – 5 )=> 123+4*+ 5-

The suffix expression is :12 3 + 4 * + 5 –

版权声明
本文为[Shura God Tang San]所创,转载请带上原文链接,感谢